Desain Arsitektur Sistem Parkir Otomatis Dengan Arduino Uno Pada Scientia Residences Tangerang - Aris Aris; Ferry Ardiyanto; Erika Septiyanti (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
Automated parking systems are indispensable in managing parking and to facilitate the management of parking areas. The existing parking system at Scientia Residences Tangerang is still carried out by entering the vehicle number into the computer by the operator, then printing, this means that the parking ticket given to residents and guests of Scientia Residence Tangerang is in the form of parking paper containing the vehicle number and data when the vehicle entered the parking lot. in these residences. Problems occur when parking attendants carry out parking transactions which are prone to data input errors and other errors. Making an automatic parking system is the best choice to provide solutions to existing problems. The final result of this research is the architectural design of an automatic parking system that uses Arduino Uno to be implemented at Scientia Residences Tangerang with the aim of saving time and improving the performance of the parking attendants of the residences.